Concentration of dioxin and screening level ecotoxicity of pore water from bottom sediments in relation to organic carbon contents - Baran, Agnieszka (Ecotoxicology (London, England), 2021)
The information about concentrations of dioxin in pore water, ecotoxicity and DOC and TOC content can be key factor for the prediction of the fate of dioxins in the aquatic environment as well as an ecological risk assessment. The aims of the study were to assess the concentration of PCDDs/PCDFs and ecotoxicity of pore water and to compare above results in relation to the dissolved organic carbon (DOC) and total organic carbon (TOC) content. The concentration of dioxins was assessed using an enzyme-linked immunoassay test, while the ecotoxicity of pore water was determined using a crustacean Daphnia magna and bacteria Aliivibrio fischeri. The studies were conducted on two different dammed reservoirs Rożnów (catchment basin of an agricultural character) and Rybnik (catchment basin of an industrial character) located in southern Poland. The concentration of dioxins in pore water was between 8.56 to 90.92 ng EQ/L, with a significantly higher concentration in the pore water from the Rożnów Reservoir than the Rybnik Reservoir. The DOC content in pore water was from 30.29 to 63.02 mg/L (Rożnów Reservoir) and from 35.46 to 60.53 mg/L (Rybnik Reservoir). Higher toxic responses were recorded for A. fischeri than for D. magna. Moreover a significantly higher toxicity for both tested organisms was indicated in pore water from the Rożnów Reservoir. Besides of TOC and DOC, the fine fractions of the sediments were particularly important in the concentration of dioxin in pore water. The other pore water parameters, such as pH and EC can influence the toxicity of water for organisms. The result indicate complex relationships between the PCDD/F, ecotoxicity and DOC, TOC concentration in pore water and confirms that these parameters are important in terms of water environmental contamination